An analysis of soy milk physical resistance exposed to extremely low frequency (ELF) magnetic fields of 300 μT and 500 μT intensities - Sudarti, Sudarti; Widjayanti, Octavia Dwi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
Several studies have reported that exposure to ELF magnetic fields can increase cell death and inhibit bacterial proliferation. This study aimed to analyze the resistance of soy milk exposed to ELF magnetic fields with 300 μT and 500 μT intensities. The researchers employed a completely randomized design. The soy milk samples were exposed to ELF magnetic fields intensities of 300 μT and 500 μT for 60, 90, and 120 minutes. The variables studied were physical resistance (aroma, color, texture, and clot formation), pH, and density. The physical condition data were analyzed descriptively, while the pH and density data were analyzed using Mann Whitney and Kruskal Wallis statistics. The results showed that the aroma, texture, and clot formation on the surface of the samples exposed to the 500 μT intensity were better than the control group until ten hours after exposure. However, the color was not different from the control group. Therefore, exposure to ELF magnetic fields intensity of 500 μT potentially increased the soy milk resistance. The research results can be used as the basis for developing food security technology with ELFelectromagnetic wave radiation.